Citizen engagement in print media: A study of SMSes published in The Namibian (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
This paper explores the content and communication acts of text messages in the form of SMSes written by Namibian citizens and published daily under “What you’re Saying!” in The Namibian. Its main aim is to provide insights into the realities of the population at grassroot-level, which are brought to light via the medium of the newspaper. Using the theoretical framework of Medium theory and theory of Cultural Hegemony, this paper argues that citizen engagement via SMS discloses how  public communication contributes to press freedom, problem solving and nation-building in Namibia. The “What you’re saying” platform enables alternative and activist citizen participation in the discussion of their choice. This study used 286 SMSes to identify areas of concern of Namibian citizens. The study’s objectives were to presents issues, such as eduation, health, or service delivery  directed to entities in the public and private sector, Further objectives include sub-themes, and communication acts, such as criticism, information-giving, complaint, suggestion, question, request, review and praise. The analysis discusses frequency of keywords in relation to the themes and sub-themes used. The findings are related to services and governance. Another feedback mechanism might be required to show responses to legitimate concerns.
Keywords: Namibia; SMS; The Namibian; citizen engagement; print media; press freedom